Critical state modeling of lower-bound threshold stress for clay subgrade - Loh, Richard; Nikraz, Hamid (Kasetsart University, Thailand, 2012)
Railway track foundation with fine-grained subgrade, under loading of cyclic nature, can build up excess pore pressure and results in progressive shear failure at a stress level less than its static undrained strength. It is widely accepted a threshold stress level exists, where loading above such level causes large deformation; otherwise stability of vertical track profile will be assured. This paper described the theoretical model that predicts the threshold stress of clay soil. The threshold stress so determined represents the lower-bound solution for bearing strength capacity of clay subgrade which normally exists in an unsaturated state. Developed from the “original Cam-clay” model and validated by series of undrained cyclic triaxial test data on reconstituted kaolin clay, the proposed theoretical model enables the prediction of threshold stress to be made from the fundamental properties of the soil, based on current state of stress and stress history of the sub-grade soil. The model reserved its ability to further expand into predicting the threshold stress of soil in its un-saturated state.